If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -5r + 8r + -6 = 10r + -11 + 2r Reorder the terms: 8 + -6 + -5r + 8r = 10r + -11 + 2r Combine like terms: 8 + -6 = 2 2 + -5r + 8r = 10r + -11 + 2r Combine like terms: -5r + 8r = 3r 2 + 3r = 10r + -11 + 2r Reorder the terms: 2 + 3r = -11 + 10r + 2r Combine like terms: 10r + 2r = 12r 2 + 3r = -11 + 12r Solving 2 + 3r = -11 + 12r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-12r' to each side of the equation. 2 + 3r + -12r = -11 + 12r + -12r Combine like terms: 3r + -12r = -9r 2 + -9r = -11 + 12r + -12r Combine like terms: 12r + -12r = 0 2 + -9r = -11 + 0 2 + -9r = -11 Add '-2' to each side of the equation. 2 + -2 + -9r = -11 + -2 Combine like terms: 2 + -2 = 0 0 + -9r = -11 + -2 -9r = -11 + -2 Combine like terms: -11 + -2 = -13 -9r = -13 Divide each side by '-9'. r = 1.444444444 Simplifying r = 1.444444444
| 4x-5(x+2)=2x-3(x+1) | | b^2-10b+25b=0 | | 6-(8-5x)=3x-8 | | -7x+4=-4x-17 | | x^3+8x-30=0 | | 6y+2(y+5)=12 | | B=870(1+0.03)9+9+9+9+9+9+9+9+9 | | q(15)=100-4*15 | | -6x-26=-12x+58 | | 6x+3x=8x-5 | | (3x/8)+1-(1x/8)=2+(5x/8)+(x/8) | | (15-9/2)^2 | | (r-6)2= | | d^2+16d+64=0 | | h(x)=-8x^3+14x-35 | | 6n-3=8n+7 | | 8a-1=2a+23 | | B=870(9+0.03) | | 6x+2+7=10 | | B=870(1+0.03)9 | | 8x-5=-29 | | 5(2x+4)=9x+5 | | B=870(1+0.03) | | 7x+2x=29 | | 3(x+4)-5=11 | | 7x+2+x=29 | | 8-2x=3x-67 | | 5x+4=3x+1+2x+3 | | (1/2x^2+5)^2 | | 3x+5x-8=0 | | 2(x-2)-1=5 | | 5m+4=3m-1+2m |